2010
DOI: 10.48550/arxiv.1009.4960
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Current trends in searches for new physics using measurements of parity violation and electric dipole moments in atoms and molecules

V. A. Dzuba,
V. V. Flambaum

Abstract: We review current status of the study of parity and time invariance phenomena in atoms, nuclei and molecules. We focus on three most promising areas of research: (i) parity non-conservation in a chain of isotopes, (ii) search for nuclear anapole moments, and (iii) search for permanent electric dipole moments (EDM) of atoms and molecules which are caused by either, electron EDM or nuclear T, P -odd moments such as nuclear EDM and nuclear Schiff moment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…An experimentally feasible approach to using APV to probe electroweak physics was first proposed in 1974, [114] and since then APV has been observed in a number of atoms [29,[115][116][117]. Here we will briefly discuss how buffer gas beams may improve experimental studies of APV; detailed discussions of APV theory and experiments may be found elsewhere [29,30,115,118].…”
Section: Parity Violation and Anapole Momentsmentioning
confidence: 99%
See 2 more Smart Citations
“…An experimentally feasible approach to using APV to probe electroweak physics was first proposed in 1974, [114] and since then APV has been observed in a number of atoms [29,[115][116][117]. Here we will briefly discuss how buffer gas beams may improve experimental studies of APV; detailed discussions of APV theory and experiments may be found elsewhere [29,30,115,118].…”
Section: Parity Violation and Anapole Momentsmentioning
confidence: 99%
“…An experimental signature of an anapole moment is then a difference in parity violating amplitudes between different hyperfine levels. So far only a single anapole moment has been measured, in the 133 Cs nucleus [121], though other experiments are underway [30].…”
Section: Parity Violation and Anapole Momentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the end of section II we introduced the notations S 1 , S 2 , S 3 and S 4 for these terms (see Eqs. (8,9,10,11)). The terms involving the p 1/2 states are S 1 and S 3 , the terms with the p 3/2 states are S 2 and S 4 .…”
Section: Accuracy Of Calculationsmentioning
confidence: 99%
“…the contribution from nuclear anapole moment (see, e.g. reviews [6,9]). The study of the PNC for a chain of isotopes does not require atomic calculations and can deliver useful information about either neutron distribution or new physics beyond standard model (see, e.g.…”
Section: Introductionmentioning
confidence: 99%